Estimation of Salivary Levels of Pro Inflammatory Cytokines (Interleukin-1α and Interleukin-8) in Iraqi Lichen Planus patients, the association of these parameters with dental plaques, gingivitis and smoking status (Mustansiria Dental Journal, 2019)
Background: Oral lichen planus (OLP) is chronic inflammatory disease of the oral mucosa whose etiology is still unknown but mounting evidence points to the immunologic basis of this disorder.The aim of the present study was to assess the level of salivary IL-1α, IL- 8, salivary flow rate (SFR), the plaque and gingival indices in lichen planus patients, and to assess their level pre and post treatment with topical steroid in study group, in addition to the assessment of relation of smoking to these parameters in oral lichen planus patients.Materials and methods: Whole saliva from fifteen (15) patients with oral lichen planus, eighteen (18) healthy persons, were investigated for the presence of IL-1 α, IL-8 by enzyme linked immunosorbent assay ( ELISA). In addition, the flow rate of saliva (SFR) measured in both groups, plaque and gingival indices also assessed pre and post treatment.Results: The results showed a significant elevation of pro-inflammatory cytokines IL-1α , IL- 8, plaque and gingival indices in study group in comparison to control group except the SFR where it was higher in control group than study group also showed that some of these parameters significantly related to smoking statues.The studies parameters also showed significant variation after using of topical steroid in which the salivary level of cytokines IL-1 α , IL-8, plaque &Gingival indices were significantly decreased after treatment except SFR was significantly increase after treatment.Conclusion: Patients with oral lichen planus have had high levels of inflammatory cytokines in their saliva. The results also showed wide variations in levels among patients in pre and post treatment with steroid, in addition the level of pro inflammatory cytokines significantly related to smoking status. The results suggest links between the proinflammatory cytokines ( IL-1 α , IL-8 ) from one side and oral lichen planus disease, medication used for treatment and smoking status of the patients from another side.